Stories of targeting: process documentation of selecting the ultra poor for CFPR/TUP programme - Zaman, Shahaduz; Matin, Imran; Rahman, Hasanur; Ali, Tariq; Noor, Marufia; Rashid, Mamum-ur-; Shihab, Abu Muhammad; Parveen, Rezvina (BRAC, 2019)
The targeting process for the CFPR/TUP (Challenging the Frontiers of Poverty Reduction - Targeting the Ultra Poor) progranune brings together diverse strands of knowledge on ·poverty (indigenous, local, progranunatic, and academic) in identifying and selecting beneficiaries (Marin and Halder 2002). The targeting process is, therefore, multi-staged and involves a variety of actors and processes. Four researchers were trained in Dhaka on qualitative research methodology with specific focus on process documentation research (PDR). They were then sent to various CFPR/TUP progranune areas to document the various stages of the targeting process. The researchers sent back 28 reports covering t 08 events/ activities/ stages to the Head Office during March t 9-April 30, 2003. These process documentation reports in their consolidated form comprise this final report...